2006
DOI: 10.1016/j.ejheart.2006.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials update from the joint European Society and World Congress of Cardiology meeting: PEP‐CHF, ACCLAIM and the HHH study

Abstract: This article provides information and a commentary on trials relevant to the pathophysiology, prevention and treatment of heart failure, presented at the joint European Society and World Congress of Cardiology meeting held in Barcelona in September 2006. All reports should be considered as preliminary data, as analyses may change in the final publication.The PEP-CHF study suggests that perindopril improves symptoms and functional capacity and may reduce heart failure hospitalisations in patients with diastolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
(17 reference statements)
0
5
0
1
Order By: Relevance
“…There was also a reduction in the number of outpatient visits in the telemonitoring group compared with usual care, but this was not significant. This and other studies of similar size [26] and duration have failed, individually, to show convincing benefit. Nonetheless, these data reinforce the results of meta‐analysis that should help define the size and nature of a definitive study.…”
Section: Home‐hf: the Home Heart Failure Study Presented By Owais mentioning
confidence: 59%
“…There was also a reduction in the number of outpatient visits in the telemonitoring group compared with usual care, but this was not significant. This and other studies of similar size [26] and duration have failed, individually, to show convincing benefit. Nonetheless, these data reinforce the results of meta‐analysis that should help define the size and nature of a definitive study.…”
Section: Home‐hf: the Home Heart Failure Study Presented By Owais mentioning
confidence: 59%
“…Therapeutic anti-TNF approaches have not been successful enough so far. Immune modulation therapy failed to reduce the incidence of all-cause mortality and cardiovascular hospitalisations in the ACCLAIM study, but the observed differences in outcome in some heart failure patients warrants further investigation [26]. However, sustained increases in cytokines, including TNF-alpha and its receptor, lead to monocyte phenotype transition, myocytic apoptosis, and activation of matrix metalloproteinase [27].…”
Section: Metabolismmentioning
confidence: 78%
“…Moreover, this study was not designed to address the important question of which specific markers of immune activation, circulating anti-cardiac antibodies, or HLA expression on cardiomyocytes are most useful in selecting subsets of patients with chronic DCM who may respond to immunomodulatory therapy. Finally, this analysis did not include the very recent ACCLAIM data examining a large study population of HF patients [19]. However, although the therapeutic option in this study may be interesting, potentially representing an immunomodulatory approach, the mechanisms of action is far from clear, with no well defined effects on the immune system, and this approach has not been proven beneficial in other immune-mediated disorders.…”
Section: Discussionmentioning
confidence: 92%